CAT1 silencing inhibits TGF-β1-induced mouse hepatic stellate cell activation in vitro and hepatic fibrosis in vivo. (December 2020) - Peng, Feng; Tian, Yi; Ma, Jing; Xu, Zhenyu; Wang, Sujuan; Tang, Min; Lei, Jianhua; Gong, Guozhong; Jiang, Yongfang
Abstract: Hepatic fibrosis is characterized by abnormal accumulation of extracellular matrix (ECM). Hepatic stellate cells (HSCs) are the primary cells that produce ECM in response to hepatic injury, and transforming growth factor-beta (TGF-β) has been regarded as the central stimulus responsible for HSC-mediated ECM production. In the present study, we attempted to identify a critical factor in HSC activation and the underlying mechanism. By analyzing online microarray expression profiles, we found that the expression of high-affinity cationic amino acid transporter 1 (CAT1) was upregulated in hepatic fibrosis models and activated HSCs. We isolated and identified mouse HSCs (MHSCs) and found that in these cells, CAT1 was most highly upregulated by TGF-β1 stimulation in both time- and dose-dependent manners. In vitro, CAT1 overexpression further enhanced, while CAT1 silencing inhibited, the effect of TGF-β1 in promoting MHSC activation. In vivo, CAT1 silencing significantly improved the hepatic fibrosis induced by both CCl4 and non-alcoholic fatty liver disease (NAFLD). In summary, CAT1 was significantly upregulated in TGF-β1-activated MHSCs and mice with hepatic fibrosis. CAT1 silencing inhibited TGF-β1-induced MHSC activation in vitro and fibrogenic changes in vivo . CAT1 is a promising target for hepatic fibrosis treatment that requites further investigation in human cells and clinical practice.